PENGARUH ROTASI JABATAN, ETOS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KHARISMA SURYA SEMESTA - Sismawati Situmorang; Achmad Fauzi; Sri Maulidia Permatasari; Anton Robiansyah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This research aims to provide empirical evidence for the impact of job rotation, professional ethics and work motivation on employee performance. The subjects of this study are employees working at PT. Kharisma Surya Semesta. The method used in this study is the use of survey and interview methods, as well as the method of distributing questionnaires (the sampling technique of this study uses census technique), which means that the interviewees used are all employees working at PT Kharisma Surya Semesta. Data collection was conducted from October 2020 to July 2020. The data analysis methods used in this study are descriptive analysis and verification analysis. The data processing in this study used structural equation modeling (SEM) analysis and the partial least squares (PLS) alternative method using Smart PLS 3.0 software. The research results provide empirical evidence that shows that job rotation, professional ethics and work motivation have an impact of 75,7% on employee performance. Further test results prove that job rotation, professional ethics and work motivation have a positive and significant impact on employee performance.